Intramolecularly Bridged Calix[4]arenes with Pronounced Complexation Ability toward Neutral Compounds - Slavík, Petr; Eigner, Václav; Lhoták, Pavel (Organic letters, 2015)
Regioselective derivatization via an organomercury intermediate allowed for the introduction of carboxylic acid functionality into the meta position of the calix[4]arene skeleton. Intramolecular Friedel-Crafts cyclization led to a novel type of calixarene containing a ketone bridging moiety. Subsequent attack of the ketone by organometallic compounds occurred selectively from outside providing tertiary alcohols with the OH group oriented inside the cavity. These compounds can complex neutral molecules both in the solid state (X-ray) and in solution (NMR) using the cooperative effect of hydrogen bonding (OH) and CH-π interactions from within the cavity.